A new species of Blatticola schwenk, 1926 (Oxyurida, Thelastomatidae) a parasite of Anurogryllus muticus (De Geer, 1773) (Orthoptera, Gryllidae) from Argentina - Achinelly, María Fernanda (2007)
Blatticola cristovata n. sp. (Oxyurida, Thelastomatidae) a parasite of the cricket Anurogryllus muticus (De Geer, 1773) (Orthoptera, Gryllidae) from Argentina, is described and illustrated. This is the first species of the genus Blatticola found parasitizing cricket. This new species is characterized in females by having the cuticle annulated through the body length, the mouth opening is subtriangular and surrounded by eight cephalic papillae, the stoma is short with three pairs placed in two rows of cuticular sclerotised plates, amphids in small pore shaped, oesophagus is divided into three parts, anterior cylindrical corpus, isthmus distinct, and basal bulb valved, the nerve ring is situated around the middle of corpus, the intestine is wide broad anteriorly, oval eggs, smooth shell, with a straight side, and the other side with a band running longitudinally. Males with one pair of preanal, one pair of adanal and two pairs of postanal papillae, and the tail appendage short, conical and pointed.